Inhalation of Cinnamon Aromatherapy (Cinnamon Burmanii) to Reduce Postpartum Pain in Normal Delivery - Iswati, Retno Setyo (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
After delivery, uterine contractions will occur, which cause pain. Postpartum pain is physiological and lasts for several days after the delivery process. Postpartum pain that is not handled properly and correctly can cause discomfort, including disrupting activities, disturbing the mother's rest time, or when breastfeeding, and can cause trauma. Handling postpartum pain using cinnamon aromatherapy inhalation can be an alternative to non-pharmacological therapy. Cinnamon contains the main compounds, namely cinnamaldehyde and eugenol, which have anti-inflammatory effects and can reduce pain. In addition, the content of essential oils helps relax tense muscles, increase circulation, and relieve stomach cramps. The study aimed to determine the effectiveness of cinnamon aromatherapy inhalation in reducing postpartum pain in normal delivery. The type of research is Quasy Experimental with a pre-test and post-test design. The research sample consisted of 30 postpartum mothers divided into control and intervention groups. The sampling technique was purposive sampling. The research instrument used was the Visual Analague Scale (VAS), which measured the pain level, and an observation sheet. Cinnamon inhalation was given to the intervention group by dripping cinnamon onto a tissue and inhaling it at a distance of plus minus 1 cm from the nostrils for 30 minutes starting 6 hours postpartum until the 3rd day. The control group was given deep breathing relaxation, starting 6 hours postpartum and continuing until the 3rd day. Data analysis used the Mann-Whitney test. The results of the Mann-Whitney test showed a p-value of 0.001. Cinnamon aromatherapy inhalation is effective in reducing postpartum pain in normal delivery